Transformasi Qris sebagai Instrumen Pembayaran Digital dalam Perspektif Ekonomi Syariah - Ade Suryawirawan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
The rapid expansion of digital payment systems in Indonesia is reflected in a 198.7% increase in Quick Response Code Indonesian Standard (QRIS) transactions during the first quarter of 2025, involving over 53 million active users and 34 million registered merchants. This study aims to examine the integration of financial technology with Islamic economic principles and to develop a digital financial services framework based on maqashid shariah. As a modern payment instrument, digital money offers efficiency, flexibility, and robust security features. However, its implementation must adhere to Islamic legal principles, particularly by avoiding riba (usury), gharar (uncertainty), and other prohibited elements. Fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) serve as fundamental references to ensure the sharia compliance of digital financial transactions. Contracts such as mudharabah, musyarakah, and wakalah are frequently employed in Islamic fintech to maintain alignment with Islamic legal norms. This research adopts a qualitative descriptive approach, utilizing data from academic literature, Islamic finance sources, and regulatory documents related to digital payment systems. The findings emphasize QRIS’s substantial role in advancing Islamic financial inclusion, enhancing transaction security, and broadening public access to sharia-compliant financial services. This study contributes to the ongoing discourse on fostering an equitable, ethical, and competitive digital financial ecosystem grounded in maqashid shariah principles.